ADAMTS9-Mediated Extracellular Matrix Dynamics Regulates Umbilical Cord Vascular Smooth Muscle Differentiation and Rotation - Nandadasa, Sumeda; Nelson, Courtney M.; Apte, Suneel S. (Cell reports (Cambridge), 2015)
Despite the significance for fetal nourishment in mammals, mechanisms of umbilical cord vascular growth remain poorly understood. Here, the secreted metalloprotease ADAMTS9 is shown to be necessary for murine umbilical cord vascular development. Restricting it to the cell surface using a gene trap allele, Adamts9Gt, impaired umbilical vessel elongation and radial growth via reduced versican proteolysis and accumulation of extracellular matrix (ECM). Both Adamts9Gt and conditional Adamts9 deletion revealed that ADAMTS9 produced by mesenchymal cells acted non-autonomously to regulate smooth muscle cell (SMC) proliferation, differentiation, and orthogonal reorientation during growth of the umbilical vasculature. In Adamts9Gt/Gt, we observed interference with PDGFRβ signaling via the mitogen-activated protein kinase/extracellular signal-regulated kinase (MAPK/ERK) pathway, which regulates cytoskeletal dynamics during SMC rotation. In addition, we observed disrupted Shh signaling and perturbed orientation of the mesenchymal primary cilium. Thus, ECM dynamics is a major influence on umbilical vascular SMC fate, with ADAMTS9 acting as its principal mediator. [Display omitted] •Cell-membrane ADAMTS9 suffices for gastrulation, but not for later mouse development•ADAMTS9 is required for versican proteolysis during umbilical cord vascular growth•Extracellular matrix accumulation impairs umbilical smooth muscle differentiation•Matrix dynamics regulates primary cilium orientation and Shh and PDGFRβ signaling Nandadasa et al. show that ADAMTS9, a secreted metalloprotease, is essential for versican proteolysis during mouse umbilical cord vascular development. In an Adamts9 gene trap mutant, they report non-autonomous impairment of crucial steps in smooth muscle signaling pathways and differentiation that are essential for construction of the umbilical vessel wall.